From the Past to the Future: a Milestone of Muban Chombueng Rajabhat University in Sustainable University - Siladech, Chairit; Kongtoom, Rapeepan; Rattananon, Eaimrit; Chuenjit, Atima (Journal of Sustainability Perspectives, 2023)
This paper presents a milestone of Muban Chombueng Rajabhat University in sustainability. The university was founded in 1954 with the concept of Village College. The purposes of the establishment were to provide educational opportunities for students and to solve the lack of teachers in distant areas around Thailand. The college trained teachers and practiced some skills to be community developers. Nowadays, the university is still on the pathway of sustainability. The university provides educational opportunities for all through degree programmes. Furthermore, the university has promoted the MCRU Credit Bank System for lifelong learning so that people of every background can participate in classes. As part of the community, the university cooperates with local communities to improve the quality of life and increase household income. For research and innovation, the university encourages academia and students to create projects focused on solving community problems. These projects impact society in all aspects, especially, good health and well-being. For the future, the university announces a five-year plan to demonstrate the direction of a sustainable university. The university improves curricula based on social dynamics and trains students to be global citizens. However, the decrease in new enrolment will be a new challenge. It affects the university's income also decreases. Therefore, it challenges the allocation budget to develop students and provide outreach projects. Moreover, the local communities also face the aged society, and this new challenge should be aware from all institutions. From this condition, the university is the partnership with communities to tackle these challenges and settle sustainability.